Information Technology Outsourcing: Asset Transfer and the Role of Contract - Chang, Young Bong; Gurbaxani, Vijay; Ravindran, Kiron (Management Information Systems Research Center, 2017)
Information technology outsourcing (ITO) is the predominant mode of acquiring information systems services, providing clear evidence that the economics of service delivery favor external service providers over in-house information systems departments. An interesting feature of many large ITO arrangements is that the production assets necessary for service delivery are transferred to the vendor. The argument in favor of such asset transfers, based in property rights theory, is that they are necessary to incentivize vendors to continue to invest in transaction-specific assets to improve service. On the other hand, transaction cost economics predicts that transferring such assets increases bilateral dependence and will elevate the risk of post-contractual opportunistic behavior. The contracting challenge in this context is to specify the terms of exchange to achieve the client’s objectives for outsourcing while managing the risks of asset transfer. We develop a theoretical framework to derive propositions on contract design in the presence of asset transfer. We identify the importance of contractual clauses that mitigate the associated risks and the complementary role of compensation mechanisms, specifically the pricing scheme and IT-related performance incentives. We have compiled a unique dataset that allows us to test our propositions by comparing ITO contracts that include asset transfer to those that do not. We find that asset transfer does significantly affect contract design, manifested in the inclusion of clauses that protect both clients and vendors. Outsourcing objectives are more likely to be met when contracts include compensation mechanisms that complement asset transfer.
Keywords: 12 Matemáticas::1203 Ciencia de los ordenadores; ODS 9 - Industria, innovación e infraestructura; IT outsourcing; asset transfer; contract structure; transaction cost economics; property rights; IT-related performance incentives